TAKHRIJ HADIS : ANALISIS KRITIK SANAD HADIS TANGAN DI ATAS LEBIH BAIK DARIPADA TANGAN DI BAWAH - Ernawati Beru Ginting (UIN Sumatera Utara Medan, 2020)
One branch of the science of hadith is takhrij al-hadith, through which we can trace the original source of the hadith. Because of the importance of this takhrij, the researchers tried to apply how the workings of this science. The object of this discussion is that the hadith about the hand above is better than the hand below. Through this method of takhrij, the researcher will reveal about several things related to the hadith that will be sought, namely: where the hadith is found, who the raw is, what the status of the sanad, and how the legal status in that hadith. So it is understood that the status of the narrators who narrated the hadith and also the status of the hadith. From this research it can be ascertained that the narrators whose siqah and hadith are valid and can be used as a basis in Islamic law